1970
DOI: 10.3329/jbas.v33i2.4100
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Pb(II) from Aqueous Solution by Sorption on used Tea Leaves

Abstract: Batch sorption study was performed using used black tea leaves (UBTL) as a low-cost adsorbent for the removal of lead (II) from aqueous solutions. Experiments were conducted as a function of contact time, initial metal ion concentration, solution pH and temperature. The sorption of Pb(II) on used tea leaves increases with increase of initial pH of solution upto a certain limit which corresponds to the pH nearly 5. The sorption isotherms follow Langmuir equation better than Freundlich equation. Again the Langmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The proper utilization of this used black tea leaves (UBTL) would make economical and environmental benefits. Several studies have been reported about the utilization of used black tea leaves as a biosorbent with high efficiency to eliminate organic dyes and heavy metals from water as well as from wastewater [20][21][22][23][24][25][26][27][28][29]. However, no research has been done to investigate the potential of Ethyl violet adsorption on UBTL.…”
Section: Introductionmentioning
confidence: 99%
“…The proper utilization of this used black tea leaves (UBTL) would make economical and environmental benefits. Several studies have been reported about the utilization of used black tea leaves as a biosorbent with high efficiency to eliminate organic dyes and heavy metals from water as well as from wastewater [20][21][22][23][24][25][26][27][28][29]. However, no research has been done to investigate the potential of Ethyl violet adsorption on UBTL.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is very suitable to develop low cost and efficient adsorbent, especially from wastage bio-materials like animal, vegetable and forest by-products for removal of heavy metals from wastewaters [5,6]. It was reported that rice husk [7], olive stone [8], clay minerals [9][10][11][12], used tea leaves [13], wheat straw [14], banana peel [15,16], chitin and chitosan [17] as a good adsorbent, because these are easily available and less polluting substances. It was reported that metals are attached onto the surface of adsorbent in the adsorption process [18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, adsorptions of metals by using bioadsorbents are in progress [4,5]. Different types of industrial and agricultural bio-wastes are investigated as bioadsorbent such as sugarcane bagasse [6], rice husk [7], olive stone [8], orange waste [9], used tea leaves [10], wheat straw [11], sea weeds [12], chitin and chitosan [13]. They are easily available, economically acceptable and chemically less polluting substances often with high affinity and binding capacity of metals.…”
Section: Introductionmentioning
confidence: 99%